Analisis Faktor-Faktor Yang Mempengaruhi Keputusan konusmen Dalam Melakukan Pinjaman Pada KSU Jati Diri SIMO Boyolali - Handayani, Rumyani; Nurtantiono, Andri (STIE Surakarta, 2013)
Intention of this research is : 1) To know reputation factor influence of company, loan procedure and level of service to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. 2) To know factor having an effect on most dominant to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. Hypothesis submitted is : 1) Anticipated there is influence between company reputations, loan procedure and level of service to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali; 2) Anticipated loan procedure factor to have influence very dominan to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. Population from this research is consumer (client) what does loan at KSU Jati Diri Simo Boyolali. Level of sample in this research 80 responders. Data source applied is primary data. Data collecting technique applied is observation, questionaire and documentation. Analyzer applied is validity test, reliability test, multiple linear regression, test t, F test and coefficient of determination. Based on result of analysis, hence inferential : 1) There is influence between company reputations, loan procedure and level of service to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. 2) Loan procedure factor has influence that is most dominant to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. Based on the conclusion, hence can be suggested : Management KSU JATI DIRI SIMO BOYOLALI is expected to pays attention to factors influencing decision of consumer in doing loan for example reputation of company, loan procedure and level of service.